Expression cloning of a gibberellin 20-oxidase, a multifunctional enzyme involved in gibberellin biosynthesis. - Lange, T (1994)
In the biosynthetic pathway to the gibberellins (GAs), carbon-20 is removed by oxidation to give the C19-GAs, which include the biologically active plant hormones. We report the isolation of a cDNA clone encoding a GA 20-oxidase [gibberellin, 2-oxoglutarate:oxygen oxidoreductase (20-hydroxylating, oxidizing) EC 1.14.11.-] by screening a cDNA library from developing cotyledons of pumpkin (Cucurbita maxima L.) for expression of this enzyme. When mRNA from either the cotyledons or the endosperm was translated in vitro using rabbit reticulocyte lysates, the products contained GA12 20-oxidase activity. A polyclonal antiserum was raised against the amino acid sequence of a peptide released by tryptic digestion of purified GA 20-oxidase from the endosperm. A cDNA expression library in lambda gt11 was prepared from cotyledon mRNA and screened with the antiserum. The identity of positive clones was confirmed by the demonstration of GA12 20-oxidase activity in single bacteriophage plaques. Recombinant protein from a selected clone catalyzed the three-step conversions of GA12 to GA25 and of GA53 to GA17, as well as the formation of the C19-GAs, GA1, GA9, and GA20, from their respective aldehyde precursors, GA23, GA24, and GA19. The nucleotide sequence of the cDNA insert contains an open reading frame of 1158 nt encoding a protein of 386 amino acid residues. The predicted M(r) (43,321) and pI (5.3) are similar to those determined experimentally for the native GA 20-oxidase. Furthermore, the derived amino acid sequence includes sequences obtained from the N terminus and two tryptic peptides from the native enzyme. It also contains regions that are highly conserved in a group of non-heme Fe-containing dioxygenases.